A multi-country comparison of reasons for dental non-attendance - Listl, Stefan; Moeller, John F.; Manski, Richard (European journal of oral sciences, 2014)
The purpose of this study was to describe differences across countries with respect to the reasons for dental non-attendance by Europeans currently 50 yr of age and older. The analyses were based on retrospective life-history data from the Survey of Health, Ageing, and Retirement in Europe and included information on various reasons why respondents from 13 European countries had never had regular dental visits in their lifetime. A series of logistic regression models was estimated to identify reasons for dental non-attendance across different welfare-state regimes. The highest proportion of respondents without any regular dental attendance throughout their lifetime was found for the Southern welfare-state regime, followed by the Eastern, the Bismarckian, and the Scandinavian welfare-state regimes. Factors such as patients’ perception that regular dental treatment is ‘not necessary’ or ‘not usual’ appear to be the predominant reason for non-attendance in all welfare-state regimes. The health system-level factor ‘no place to receive this type of care close to home’ and the perception of regular dental treatment as ‘not necessary’ were more often referred to within the Southern, Eastern, and Bismarckian welfare-state regimes than in Scandinavia. This could be relevant information for health-care decision makers in order to prioritize interventions towards increasing rates of regular dental attendance.
Gesehen am 25.09.2020
First published: 23 October 2013